Engineering Plant Metabolism for Enhanced Biofuel and Bioproduct Production: Current Advances and Future Prospects - Gupta, kavish (Journal of Advanced Research in Petroleum Technology & Management; Vol 9 No 1&2 (2023): Journal of Advanced Research in Petroleum Technology and Management, 2023)
Biomass, consisting of 30% xylan and 50% lignin, is a key component of biofuels and bioproducts. Researchers have developed strategies to reduce xylan and lignin content in plant stems without affecting growth. These methods use dominant genes and overexpression of genes to increase pectic galactan accumulation. The modified plants are indistinguishable from wild types under normal growth conditions. The cells of these plants have been tested for drought tolerance, showing increased resilience.